Studi Preferensi Penggunaan Transportasi Online dan Kesiapan Smart Mobility di Distrik Abepura - Ahmad A. Haruna; Monita Y. Beatrick; Marsal Arung Lamba (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The rapid growth of online transportation services has significantly transformed urban mobility patterns, including in Abepura District, Jayapura City. This study is grounded in the concept of smart mobility, which emphasizes technological integration, efficiency, and accessibility within the smart city framework. The theoretical foundation draws on consumer preference theory and the Customer Satisfaction Index (CSI) model. A quantitative approach was applied through questionnaires distributed to 100 respondents, supported by secondary data on digital infrastructure and local transport regulations. The analytical methods included conjoint analysis to identify user preferences, CSI analysis to assess smart mobility readiness, and spatial analysis to map infrastructure support. The findings indicate that fare and safety are the most influential attributes shaping user preferences, followed by application usability, transport mode, and travel time. Maxim emerged as the most widely used application, followed by Grab and Gojek. The CSI score reached 77.60%, categorized as “highly ready,” though gaps remain in intermodal integration and waiting time efficiency. Spatial analysis confirmed that the coverage of 16 BTS towers in Abepura adequately supports online transportation operations. In conclusion, online transportation services in Abepura District demonstrate strong readiness to support the implementation of smart mobility, yet further improvements are needed in modal integration and operational efficiency to ensure sustainable and inclusive urban mobility.